Excavation-induced disturbance analysis of deeply buried tunnels under three-dimensional stress: A numerical investigation - Chaojun Jia; Linyu Liu; Mingfeng Lei; Manchao He; Yingming Xiao (Transportation Geotechnics, 2026)

Numerical Investigation on the Mechanical Properties and Damage Mechanisms of Xiyu Conglomerate Under Freeze–Thaw Cycles - Yingming Xiao; Chaojun Jia; Mingfeng Lei; Ruifeng Pang; Qiang Zhang (Rock Mechanics and Rock Engineering, 2026)

In situ therapeutic vaccine gel induces pyroptosis and remodels tumor microenvironment to prevent postoperative hepatocellular carcinoma recurrence and metastasis - Liangdi Jiang; Faisal Raza; Shiqi Yang; Kunwei Li; Hang Xiao; Wenjing Chen; Jing Su; Mingfeng Qiu (Chemical Engineering Journal, 2026)

Single-step synthesis of nitrogen and phosphorus co-doped biochar and its application in dye removal: synergistic effects of adsorption and peroxymonosulfate activation - Yixuan Shi; Mingfeng Yin; Dong Liu; Xingrui Gao; Xiao Liu; Tengteng Yang; Zuoping Zhao; Xiaohui Ji; Caibin Zhao; Xianzhao Shao (Environmental Research, 2025)

Topology and element sizing optimization for performance-based design of wind sensitive tall buildings - Mingfeng Huang; Chunhe Wang; Wei Lin; Zhibin Xiao (Engineering Structures, 2025)

Genetic characterization of a novel HIV-1 circulating recombinant form (CRF162_cpx) involving CRF01_AE, CRF07_BC and subtype B in Guangdong, China - Yun Lan; Linghua Li; Mingfeng Xiao; Yaqing Lin; Xuemei Ling; Feng Li; Fengyu Hu (Virus Genes, 2025)

A leader-adaptive particle swarm optimization with dimensionality reduction strategy for feature selection - Shanshan Yang; Bo Wei; Li Deng; Xiao Jin; Mingfeng Jiang; Yanrong Huang; Feng Wang (Swarm and Evolutionary Computation, 2024)

Nitrogen Doping Engineering of V2CTx based Zinc Ion Hybrid Microcapacitors with Quadruple High Energy Density - Wei Lai; Sairao Zhao; Mengdi Guo; Di Wu; Shijun Luo; Chuankun Zhang; Tao Huang; Wenbin He; Mingfeng Li; Xin Zhou; Xiao Luo; Jian Li; et al. (Chemical Engineering Journal, 2024)

Seasonal pollution and surface characteristics of microplastics in surface water in the Wanzhou section of the Three Gorges Reservoir, China - Ying He; Qian Huang; Qilong Wang; Mingfeng Tang; Xiaoyu Lu; Fei Cheng; Guosheng Xiao (Environmental Science and Pollution Research, 2023)
The pollution of freshwater environments with microplastics (MPs) has attracted increasing attention owing to their threats to aquatic ecosystems and human health. Here, we sampled and analyzed MPs from mainstream, tributary, and backwater areas in the Wanzhou section of the Three Gorges Reservoir (TGR) in impoundment and flood periods. Microplastic pollution was the most severe in the backwater areas. The average abundance of MPs reached the highest value in the flood period (5.27±3.47×10 7 items km −2 ), which was 3–5 times that in the impoundment period. In the 0.3–5 mm size class, the 1–5 mm fraction was the most abundant, accounting for more than 81% in the flood period and 68% of the total MP particle abundance in the impoundment period in the mainstream and backwater areas. However, 0.3–1 mm MPs contributed more than 50% in the tributaries during the impoundment period. Polystyrene, polypropylene, and polyethylene MPs were detected in foam, fragment, sheet, and line-shaped MP particles. White, opaque, foamed polystyrene MPs contributed 32–81% to total MP particle abundance in the watershed. Microplastic particle surfaces showed signs of damage and oxidation, and ten different elements were found. Oxygen was clustered on the surface of foam and fragment MPs. Microplastic pollution was severe in the Wanzhou watershed. Especially in the backwater areas, oxidized MPs of variable shapes derived mainly from surface runoff in the flood period and sewage discharge in the impoundment period were abundant. The results of this study contribute to understanding seasonal pollution patterns and surface characteristics of MPs in the TGR and similar watersheds.

Exudate components exert different influences on microbially mediated C losses in simulated rhizosphere soils of a spruce plantation - Yuanshuang Yuan; Wenqiang Zhao; Juan Xiao; Ziliang Zhang; Mingfeng Qiao; Qing Liu; Huajun Yin (Plant and Soil, 2017)

Fine roots branch orders of Abies faxoniana respond differentially to warming in a subalpine coniferous forest ecosystem - Xiaozhen Pu; Chunying Yin; Qunying Xiao; Mingfeng Qiao; Qing Liu (Agroforestry Systems, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

Induction and Characterization of Adventitious Roots Directly from the Explants of Panax notoginseng - Xianfu Gao; Chunbao Zhu; Wei Jia; Wenyuan Gao; Mingfeng Qiu; Yongyu Zhang; Peigen Xiao (Biotechnology Letters, 2005)